PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZHENSHIP BEHAVIOUR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Fuji Fasisca, Rahmi Fahmy (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Organizations such as statistical institutions are under constant pressure from the need to compete, not just the need to respond quickly to changes in data and information needs. Organizations such as statistical institutions must also inspire employees to do their best and encourage employees to fulfill their performance by giving rise to OCB behavior. This study examines how organizational employees can influence them in their transformational leadership behaviors, organizational culture, organizational commitment and OCB. Total of 186 employees of a government organization participated in the study. Data were analyzed through descriptive statistics, confirmatory factor analysis and structural equation modeling. The results show that transformational leadership and organizational culture influence organizational commitment positively. Transformational leadership, organizational culture, and organizational commitment positively influence OCB. Organizational commitment does not act as a mediator between transformational leadership and OCB. Organizational commitment acts as a partial mediator between organizational culture and OCB.Keywords : Leadership Transformational, Culture Organizational, Commitment Organizational, Organiztional Citizhenship Behaviour